Narrow Banking from the Perspective of Risk - Pera, Jacek (Acta Universitatis Lodziensis. Folia Oeconomica, 2019)
The aim of this article is to identify risks arising from the attempt to stabilise the banking system with the use of narrow banking, which in practice means imposing restrictions on various types of assets held by banks and on handling current deposits. To this end, the following will be discussed: the nature and concepts of narrow banking and the risks of narrow banking. The research hypothesis is as follows: narrow banking is an effective concept to use to secure the stability of the financial system. The principal risk connected with the implementation of the concept of narrow banking results from: the cost of deposit insurance, partial loss of banks’ efficiency, mismatching of structures of assets and liabilities of the bank (resulting in GAP), as well as the size and structure of loans for the non‑financial sector. As a result of the conducted analysis, 6 indirect risks were identified, each for the assumed risk level: low, medium and high.